Crianças surdocegas, corpo & linguagem - Bezerra, Luiz Carlos Souza (2016)
This research looks at the effects of sense privation in the relationship between mothers and deaf-blind children. In order to achieve such a goal, the discussion was carried out having as basis the psychoanalytical conception of body. Considering the status of the body in Freudian Psychoanalysis made it possible to reflect on a motherchild relationship that influences directly the constitution of the erogenous body. The fundamental research matters are first laid out and after that the implications of deafblindness as a unique condition that results in a double sense privation are discussed. The discussion is brought to the field of Psychoanalysis as the outcome of the adoption of the hypothesis that looking at deaf-blind children from the viewpoint of sensorial imperfection and of the marks of the real in the body is the same as not taking into consideration essential aspects for the discussion on the uniqueness of the subject. The concept of “child as a pulsional body” was thus drawn on from the work of Cláudia de Lemos on “child phrases”. It was by the contact with those “phrases” that the subject-matter “child” emerged. Phrases in which, at first glance, traces of alienation regarding what other people say seem to be predominant, and which are, at second glance, characterized by mistakes and unusual constructions. In order to respond to the questions on the psychological and epistemic subject and, above all, to find answers to the questions about the child, De Lemos finds in Psychoanalysis the conception of pulsional body, which is consistent with the data she obtained by means of empirical research. This conception will be discussed with the aid of the works by Freud, mainly those that deal with the sex theories of children, because children, as Freud and De Lemos (1992; 2003) see them, are subjects constituted in the relationship with their mothers’ otherness; a child that is interrogated by their questions on child sexuality. In a second moment of the research, the status of the body in the theoretical elaborations of Freud was questioned. The questioning is based on the child sexuality and supports, like Freud and Lecraire, a conception of erogenous body. Freud, by proposing the theory of sexuality, identifies a discontinuity regarding biology that is brought to the relation unconscious-pulsion and to the relation with sexual pleasure, which is not restricted to genitals but connected to unconscious desire. The mother-baby relation is thus permeated by the motherly want for sexual pleasure, as the mother “looks at the child with feelings derived from her own sex life” and treats them as the “substitute of an entirely legitimate sex object” (FREUD, [1905] 1996, p. 211). According to Freud, the relation between the child and the other is that of survival, dependence, and constitution, the libidinal investment on the child body made by the Other-mother being noteworthy. There is, according to Psychoanalysis, an erogenous body which is constituted in the Other/other relation and has no unity, no hierarchy, and no organization. It is a body that designates a dispersion, not a unity (LECLAIRE, 1992, 2007). This theoretical discussion draws on a reading by De Lemos (1992, 2003) of the relation holding between body, language, and capture, with the objective of providing understanding on the implications of the Other-mother in the constitution of the body and of the language. At a third moment, some segments of interviews with four mother of deaf-blind children are discussed. The research suggests that deaf-blindness has multiple effects in the imaginary representation of mothers of deaf-blind children and that in some cases these effects may influence the libidinal investment in the body